Low-level Plasmodium vivax exposure, maternal antibodies, and anemia in early childhood: Population-based birth cohort study in Amazonian Brazil. - Anaclara Pincelli; Marly A Cardoso; Maíra B Malta; Igor C Johansen; Rodrigo M Corder; Vanessa C Nicolete; Irene S Soares; Marcia C Castro; Marcelo U Ferreira; MINA-Brazil Study Working Group (Public Library of Science (PLoS), 2021)
Background Malaria causes significant morbidity and mortality in children under 5 years of age in sub-Saharan Africa and the Asia-Pacific region. Neonates and young infants remain relatively protected from clinical disease and the transplacental transfer of maternal antibodies is hypothesized as one of the protective factors. The adverse health effects of Plasmodium vivax malaria in early childhood-traditionally viewed as a benign infection-remain largely neglected in relatively low-endemicity settings across the Amazon. Methodology/principal findings Overall, 1,539 children participating in a birth cohort study in the main transmission hotspot of Amazonian Brazil had a questionnaire administered, and blood sampled at the two-year follow-up visit. Only 7.1% of them experienced malaria confirmed by microscopy during their first 2 years of life- 89.1% of the infections were caused by P. vivax. Young infants appear to be little exposed to, or largely protected from infection, but children >12 months of age become as vulnerable to vivax malaria as their mothers. Few (1.4%) children experienced ≥4 infections during the 2-year follow-up, accounting for 43.4% of the overall malaria burden among study participants. Antenatal malaria diagnosed by microscopy during pregnancy or by PCR at delivery emerged as a significant correlate of subsequent risk of P. vivax infection in the offspring (incidence rate ratio, 2.58; P = 0.002), after adjusting for local transmission intensity. Anti-P. vivax antibodies measured at delivery do not protect mothers from subsequent malaria; whether maternal antibodies transferred to the fetus reduce early malaria risk in children remains undetermined. Finally, recent and repeated vivax malaria episodes in early childhood are associated with increased risk of anemia at the age of 2 years in this relatively low-endemicity setting. Conclusions/significance Antenatal infection increases the risk of vivax malaria in the offspring and repeated childhood P. vivax infections are associated with anemia at the age of 2 years.